The Effect of Promotion, Price Perception, and Service Quality on Purchase Decisions (A Study of Shopee Users in West Jakarta Area) - Zaky, Teuku Muhammad Ilham; Putra, Andriansyah Bachtillah (Dinasti Publisher, 2025)
The role of the Internet in economic growth is very important for both industry and individuals. The ease of accessing the internet has given birth to e-commerce, which has now become an alternative option in online shopping. E-commerce has changed the way consumers shop, reaching more consumers, and facilitating online shopping habits. This study aims to examine the effect of promotions, price perceptions, and service quality on consumer purchasing decisions at Shopee users in West Jakarta. The population in this study were all consumers who had used or purchased the Shopee application, totaling 140 people. From this research, the independent variables consist of Promotion, Perceived Price, and Quality of Service and the dependent variable is Purchase Decision. Data analysis techniques used in this study include outer model testing (Convergent Validity, Discriminate Validity, Composite Reability), Inner model hypothesis testing (R square value, Goodness of Fit Model boostraping). Data is collected by distributing questionnaires to consumers and processed using the program Smart PLS 4.0. This study proves that promotion has a positive and significant effect on purchasing decisions. Price perception has a positive and significant effect on purchasing decisions. Service Quality has a positive and significant effect on purchasing decisions.